Is S-Adenosyl Methionine (SAMe) for Depression Only Effective in Males? A Re-Analysis of Data from a Randomized Clinical Trial - Sarris, J.; Price, L. H.; Carpenter, L. L.; Tyrka, A. R.; Ng, C. H.; Papakostas, G. I.; Jaeger, A.; Fava, M.; Mischoulon, D. (Pharmacopsychiatry, 2015)
Objective: The aim of this study was to examine whether gender differences may have affected treatment response to S-adenosyl methionine (SAMe) in a recent failed randomized clinical trial (RCT) for adults with major depressive disorder.Methods: Data from a 2-site, 12-week, double-blind RCT (n=189) assessing the efficacy of SAMe vs. placebo and a comparator selective serotonin reuptake inhibitor (escitalopram) were subjected to post-hoc analyses to evaluate effects of patient gender on treatment response.Results: When assessing the efficacy outcomes within each gender separately, SAMe was superior to placebo among males (n=51), but not among females (n=62). Males showed a significant reduction of depression severity from baseline to study endpoint on the 17-item Hamilton Depression Rating Scale (4.3 point difference; p=0.034; d=0.95), while females did not show significant change. This finding emerged despite equivalence on baseline measures of depression severity between the gender groups.Conclusion: Results of this secondary data analysis suggest that gender might impact the antidepressant efficacy of SAMe, with greater therapeutic effect found in males. The underlying mechanism is still relatively unknown. Further work is needed to replicate this observation in independent samples.Clinicaltrials.gov identifier: NCT00101452
Keywords: S-adenosyl methionine; SAMe; antidepressant; gender; depression; RCT; one-carbon cycle